Bilogy, life cycle and phylogeny of malacosporeans in fish and bryozoans - Hrabcová, Martina (Jihočeská univerzita, 2015)
Malacosporeans (Myxozoa) comprising only three nominal species, cycle between vertebrate (fish) and invertebrate (bryozoans) host in freshwater aquatic ecosystems. This thesis is focused on in vitro cultivation of bryozoans, using algal cultures in order to investigate malacosporean life cycles via transmission experiments. Moreover, the biodiversity, prevalence, distribution, habitat/host preference and phylogenetic trends of malacosporeans in freshwater fish hosts are scrutinized using light microscopy and molecular methods. The potential existence of malacosporeans in marine bryozoans is also investigated.
Bilogy, life cycle and phylogeny of malacosporeans in fish and bryozoans